Comparative Advantage and Cost Efficiency of Rice-Producing Farms in Bangladesh: A Policy Analysis - Mohammad Ariful Islam (Journal of Rural Problems, 2016)
This study aims to investigate whether Bangladesh rice still has comparative advantage if fertilizer subsidy is lifted up, and to what extent the reduction of cost inefficiency raise comparative advantage. For that purpose, we calculate “Domestic Resource Cost (DRC)” as an indicator of comparative advantage, and estimate “cost inefficiency indicator” applying stochastic cost efficiency approach, using Bangladesh Integrated Household Survey data. Based on these indicators, we estimate the impacts of abolishing fertilizer subsidy program and improving cost efficiency on comparative advantage of Bangladesh rice. The results of analyses show; 1) dry season rice has comparative advantage while wet season rice does not, if fertilizer subsidy program is abolished; 2) if fertilizer subsidy is abolished, comparative advantage in overall rice production vanishes; 3) improvement of cost efficiency has positive effects on retrieving comparative advantage even if fertilizer subsidy program is abolished. These findings suggest that there is a scope for Bangladesh to increase global competitiveness by increasing cost efficiency of the rice farms targeting gradual reduction of input subsidy. – – 本稿の目的は，バングラデシュ稲作が，肥料補助金を撤廃しても比較優位を持ち続けられるか，費用非効率性の低減により，どの程度比較優位が回復するかを検討することにある．そのため，本稿では，家計調査データを用い，国内資源費用（DRC）と，確率的フロンティアモデルによる費用非効率性とを推計したうえで，肥料補助金の廃止が比較優位指標におよす影響と，費用効率性の改善が稲作の比較優位におよぼす影響とを検討する．主要な分析結果は，1）乾季稲作は比較優位を持ち雨季稲作はそれを失っていること，2）肥料補助金が廃止された場合，稲作全体の比較優位は消滅すること，および，3）費用効率性の改善は，たとえ肥料費補助金が廃止されても，費用効率性の改善により，比較優位を回復し得ること，である．これらの分析結果は，肥料補助金を削減しても費用効率性を高めることにより，バングラデシュ稲作の国際競争力を向上させる可能性を示唆するものである．
Keywords: 330; input subsidy; drc; shadow price; rice policy; cost efficiency